PEMBUATAN BUKU MAKANAN TRADISIONAL SURABAYA SEBAGAI UPAYA PELESTARIAN PRODUK LOKAL - Eliazer, Stefanus Lutfi; Bahruddin, Muh; Aziz, Abdul (Jurnal ArtNouveau, 2013)
The design goal as preserving local products and a bridge to the limited information about the existence of traditional foods in Surabaya. Then the production of this book was done by interview, observation, literature and existing studies are useful for determining the design concept. Through analysis of the theme of concept design is obtained Rescue Culture. The concept of the stretcher to be a theme in the book-making, and taking pictures, which showed that most of the traditional food is all around us. Results of a book deal is expected to help increase public awareness that it is important to preserve the local product with regard to its existence.